Religious Ethics on Industrialization: A Quranic Perspective - ZainanNazri, Mohd Khairul Nizam; Ahmad, Mahmud; Zainan Nazri, Nurul Jannah; Mat Ishak, Mardiana (Jurnal Usuluddin, 2011)
This study looks at the Quranic teaching, which apparentllt give a./ull meaning and ethics on industrialization. Islam encourages industrialization ctnd sets its pristine teachings as enshrined in the Qur’an and Sunnah of the Prophet PBt-lH as the guiding principles and values for Muslims to create a kind of industrialization that shall bring about not only economic prosperity and sustainrtble development to the nation, but also one that is in harmony with the environment. The main objective,s o.f this research are to investigate Quranic point of’ view about the industrialization and relate it to both Western and Islamic perspectives. Its main eruphasi,s is to identify the driving philosophy behind the process oJ- indttstrialization implemented in Malaltsia with the universal values and teachings o’l’Islam. This research is conducted through primarily oJ’historical approach and relies on libraryt research in order to achieve its obiectives. A textual and critical analysis of’ Quranic verses will be utilized to demonstrate the application o/ Qur’an pertaining industrializcttion. Apart from that, this study will attempt to present the concept of industrialization from the Quranic point of view with special reference to selected Quranic ’verses. The ideas presented could be further developed and appreciated by the society in promoting sustainability environment in this industrialization era.